Как Маша стала большой: [рассказы и сказки] / Е. А. Пермяк ; художник А. Шахгельдян - Пермяк Евгений Андреевич (Страна детства, 2006)
Экземпляры: ф.5 (2008) / Инвентарный номер: 52329 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: П 27 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6-4